Vander's human physiology the mechanisms of body function - Widmaier, Eric P.; Raff, Hershel, 1953-; Strang, Kevin T. (McGraw-Hill, 2014)
Vander's Human Physiology, thirteenth edition, carries on the tradition of clarity and accuracy, while refining and updating the content to meet the needs of today's instructors and students. The thirteenth edition features a streamlined, clinically oriented focus to the study of human body systems. It has also responded to reviewer requests for more clinical applications. Physiology Inquiries are maintained throughout the chapters. These critical-thinking questions associated with figures are just one more opportunity to add to the student's learning experience.